The Management of Complicated Crown Root Fracture in Equine Molar: A Case Report - Taesuji, Machimaporn; Chinkangsadarn, Teerapol (Journal of Mahanakorn Veterinary Medicine, 2020)
Equine dental disease such fracture tooth required correct technique and right equipment to achieve the best outcome. A sixteen years old warmblood gelding presented with loss of appetize and change of riding behavior. The oral examination using oral endoscope and radiographic image was carried out under standing sedation using combination of Detomidine hydrochloride and Butorphanol tritate. The diagnosis was complicated crown and root fracture of , the tooth was successfully removed using Steinmann pin repulsion technique (SPR) after failure of others technique. After one month post-operatively, the horse recovered well without any sign of sinusitis. SPR should be the last resort for removing equine tooth due to high rate of complication such recurrent sinusitis, remaining of root fragment, and extraction of non-disease tooth. In order to minimize complication, the horse must be under heavy sedation with local anesthesia (infraorbital nerve block for this case) then the disease tooth was located, and pins guided using radiograph. Post-operative care includes oral rinse with Chlorhexidine gluconate, oral medication of long-term broad-spectrum antibiotic, and nonsteroidal anti-inflammatory drug.